Three-dimensional Gait Analysis: Current Status and Future Developments - Yanxin ZHANG (康复学报)
Recent breakthroughs in measurement technology and software development make it possible to describe human movements from joint level to musculoskeletal level by biomechanical methods. In the medical field, three-dimensional gait analysis technique has been widely used in clinical diagnosis, analysis of abnormal motion patterns, evaluation of rehabilitation therapy, and optimize the rehabilitation treatment program. This paper introduces the basic concepts of gait analysis, clinical applications, and the current status and research progress in gait analysis.